Addressing social function in the treatment of depression: A call for holistic approaches - Tabara, Muhammed Fatih (Baishideng Publishing Group Inc, 2025)
This article discusses the importance of addressing social functioning impairment in patients with residual depressive symptoms, as highlighted in the study by Liao et al. The authors showed that social dysfunction persists in many patients despite symptom remission. This observation calls for a shift in depression treatment strategies, with an emphasis on integrating social functioning as a key treatment goal. This article suggests targeted interventions that focus on both symptomatic relief and the restoration of social function.
Keywords: Social function; Depression; Residual symptoms; Treatment; Psychotherapy; Cognitive-behavioural therapy